Immune Cell Proinflammatory Microenvironment and Androgen-Related Metabolic Regulation During Benign Prostatic Hyperplasia in Aging - Cao, Dehong; Sun, Ruonan; Peng, Lei; Li, Jinze; Huang, Yin; Chen, Zeyu; Chen, Bo; Li, Jin; Ai, Jianzhong; Yang, Lu; Liu, Liangren; Wei, Qiang (Frontiers in Immunology, 2022)
To review the role of inflammation in the occurrence and development of benign prostatic hyperplasia (BPH), we searched PubMed for the latest published articles up to February 2021 information using the following key words: "benign prostatic hyperplasia", "inflammation", "pathogenesis" and "disease development". Articles were obtained and reviewed to provide a systematic review of the current progress of the role of inflammation in the pathogenesis and progression of BPH. Inflammation contributes to the initiation and maintenance of unregulated cell proliferation, and is closely related to the occurrence and development of BPH. Its action pathways include tissue damage and subsequent chronic healing, autoimmunity, and co-action with androgens. During the progression of inflammation, macrophages, interleukin-8 (IL-8), interleukin-1 (IL-1) and other inflammatory-related substances aggregate locally and cause BPH through various biochemical pathways. At the same time, BPH can also counteract and inflammation to expand its scope and aggravate the situation. Inflammation can independently affect the development of BPH through a variety of ways, and it can also interact with androgens. In the course of treatment, early intervention in the occurrence and development of inflammation in prostate tissue can slow down the progress of BPH. The combination of standard therapies and anti-inflammatory measures may provide valuable new ideas for the treatment of BPH.